Evaluation of the reliability and validity of the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) in paediatric cutaneous lupus among paediatric dermatologists and rheumatologists. (1st January 2019) - Kushner, C.J.; Tarazi, M.; Gaffney, R.G.; Feng, R.; Ardalan, K.; Brandling‐Bennett, H.A.; Castelo‐Soccio, L.; Chang, J.C.; Chiu, Y.E.; Gmuca, S.; Hunt, R.D.; Kahn, P.J.; et al.
Summary: Background: The Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) is a reliable outcome measure for cutaneous lupus erythematosus (CLE) in adults used in clinical trials. However, it has not been validated in children, limiting clinical trials for paediatric CLE. Objectives: This study aimed to validate the CLASI in paediatrics. Methods: Eleven paediatric patients with CLE, six dermatologists and six rheumatologists participated. The physicians were trained to use the CLASI and Physician's Global Assessment (PGA), and individually rated all patients using both tools. Each physician reassessed two randomly selected patients. Within each physician group, the intraclass correlation coefficient (ICC) was calculated to assess the reliability of each measure. Results: CLASI activity scores demonstrated excellent inter‐ and intrarater reliability (ICC > 0·90), while the PGA activity scores had good inter‐rater reliability (ICC 0·73–0·77) among both specialties. PGA activity scores showed excellent (ICC 0·89) and good intrarater reliability (ICC 0·76) for dermatologists and rheumatologists, respectively. Limitations of this study include the small sample size of patients and potential recall bias during the physician rerating session. Conclusions: CLASI activity measurement showed excellent inter‐ and intrarater reliability in paediatric CLE and superiority over the PGA. These results demonstrate that the CLASI is a reliable and valid outcome instrument for paediatric CLE.